THE ROLE OF BIG DATA IN ENHANCING TAX COMPLIANCE IN INDIA - M B Bagadi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The rapid advancement of digital technologies has revolutionized the way governments manage tax systems worldwide. In India, the integration of big data has emerged as a powerful tool in enhancing tax compliance and combating tax evasion. Big data refers to the vast volumes of structured and unstructured data generated from multiple sources such as financial transactions, e-commerce platforms, social media, property records, and government databases. Through advanced data analytics, machine learning, and artificial intelligence, tax authorities are now able to process and analyze this data to identify discrepancies, detect tax evasion, and ensure greater accountability in the tax system. This paper explores the critical role that big data plays in improving tax compliance in India. It highlights how initiatives such as the Goods and Services Tax (GST) Network, Project Insight, and the integration of Aadhaar and PAN have strengthened the government’s ability to monitor financial activities and track non-compliant entities. Case studies including the crackdown on fake GST invoices, post-demonetization cash deposit analysis, and detection of shell companies demonstrate the practical application and success of big data in curbing tax evasion. The study also discusses how big data has contributed to widening the tax base by identifying individuals and businesses operating outside the formal tax system. Furthermore, the use of big data has enhanced taxpayer services, improved transparency, and fostered voluntary compliance by reducing human intervention and providing real-time feedback. Despite its benefits, the paper acknowledges challenges such as data privacy concerns, the quality of data, and the need for continuous technological upgradation. Nevertheless, big data remains an indispensable component of India’s evolving tax administration. The paper concludes that with the right policy framework, technological infrastructure, and data governance mechanisms, big data can significantly strengthen tax compliance and contribute to India's economic growth.